Rain attenuation prediction of optical wireless system in tropical region - Ahmad Zabidi, Suriza; Islam, Md. Rafiqul; Wajdi, Al Khateeb (2013)
Optical wireless system is a communication alternative for the last segment to where fiber optic is unable to reach due to deployment and cost constraint. An optical wireless capability is similar to optical fiber systems which provides for a high speed and a higher bandwidth link. Other features of optical wireless system are higher speed, low cost and time of deployment and broader broadband technology. However, the availability of optical wireless transmission is very much weather dependent.In temperate region fog and snow are the two restrictive of the link propagation availability. In tropical region however heavy rain is expected to be the limiting factor of optical wireless link availability. The effect of rain on optical wireless link is expressed in term of specific rain attenuation. Available specific rain attenuation parameter of optical wireless link is formulated from data measured in temperate regions. Therefore, the main objective of this research is to predict and propose specific rain attenuation parameter that best fit tropical region using measured data in tropical region for optical wireless system.